Healthcare design basics - Karlen, Mark; Roberts, Saglinda; Tucker, Kyra Krotec (Hoboken, New Jersey : John Wiley & Sons Inc., 2023)
'The purpose of this book is to provide a single resource aimed at upper level undergraduate or beginning graduate students in Interior Design or Architecture programs wishing to understand Healthcare Design in a conventional studio setting. It is the hope that it can also provide a resource as the student moves into their professional career. The book primarily examines ambulatory facilities and the spaces that are typically included within those facilities. It covers a variety of typical medical specialties, clinics and ambulatory care facilities typically within the 5,000 square foot range. Hospital settings or large long term care facilities are not covered here, although, because they are familiar to so many, typical hospital rooms are examined in some detail in Chapter 10. The book is set up to lead the student step-by-step through the design of a range of typical healthcare facilities. The chapters are organized to logically establish a design process starting with the underlying rationale or goals of specialized practices and then move on to holistically analyze the needs of the patients, medical and general staff, as well as visitors. This approach enables the designer to develop spaces that efficiently accommodate the functional aspects required to provide optimum medical treatment as well as meet the emotional, psychological and physiological needs of all stakeholders. (look at defining, it is covered in following chapters) The users of this book are expected to possess basic knowledge and skills of design, drafting and space planning. Design exercises can be completed either as hand drawn or with the use of computer drafting. Projects are designed to be developed and used in a studio classroom setting or independently'--
Includes bibliographical references and index.
Keywords: Health facilities -- Design; Health facilities -- Decoration; Hospital buildings -- Design; Interior architecture